IMPACT OF RCEP ON TRADE BALANCE AND INDONESIA’S POTENTIAL EXPORT - Diyouva Christa Novith; Aditya Subur Purwana (Unit Penerbitan Politeknik Keuangan Negara STAN, 2023)
The signing of RCEP has captured global attention for the new mega trade deals. Expected to open wider market potential and access, yet the previous trade agreements between ASEAN and its five partners raise whether RCEP can increase trade between partners. This study employed partial equilibrium using SMART Simulator to analyze the impact of RCEP on members, and identifying potential export for Indonesia. The data used is trade value between RCEP signers in 2019 and conducted two scenarios. First, one hundred percent tariff liberalization was conducted and the second simulation was conducted with consideration of sensitive list and tariff rate quotas in schedule of tariff commitments of each member. This study indentified potential Indonesian export commodities using spatial analysis and descriptive analysis in order to map each province’s potential, enhance export activities and increase the utilization rate of trade facilities. The results of this study concluded that ASEAN relatively gained lower compared to ASEAN partner countries. Australia would be the top gainer. RCEP slightly might increase the value of exports, imports and trade balance for Indonesia but the low utilization of trade facilities needs the government's attention to encourage business actors to increase productivity and reach a wider market.